Aprendizagem da docência de professoras iniciantes em um programa de mentoria: processos reflexivos e autonomia - Machado, Micheli Fernanda (2023)
This doctoral thesis aims to analyze and comprehend the reflective processes and autonomy in the teaching learning of early-career teachers participating in the Hybrid Mentoring Program (PHM). The PHM was a research intervention that had the financial support of FAPESP and was developed from a constructive-collaborative perspective, combining both in-person and distance activities within a virtual learning environment (VLE) on the Moodle platform, through the UFSCar Professors Portal. In PHM, mentors (experienced teachers with over 10 years of experience) helped beginning teachers (with up to five years of experience) in their professional development. The methodology employed is qualitative and relies on descriptive and interpretative analysis of the narratives from novice teachers and mentors, both individual productions and the record of interactions in the PHM that constituted the data source. The results reveal that the Program has made significant contributions to the professional development of the participants. It was verified that the partnership established between novice teachers and mentors provided the teachers with help in situations of coping with the difficulties present in the school context and, by being inserted in reflective processes, they were able to rethink their own practices in a collaborative way, a fundamental factor in becoming an autonomous professional. The importance of programs like this was perceived as a subsidy for the elaboration of public policies that can contribute to the professional development of teachers throughout their careers. The narratives as a process of investigation and reflection proved to be important means to understand the contributions of the Hybrid Mentoring Program in building the autonomy of teachers at the beginning of their careers, the reflection on the practices of those involved in a context of social transformations and in the education system itself, as well as contributing to research in the field of teacher education.